2002
DOI: 10.1038/sj.gt.3301684
|View full text |Cite
|
Sign up to set email alerts
|

Transient blocking of both B7.1 (CD80) and B7.2 (CD86) in addition to CD40–CD40L interaction fully abrogates the immune response following systemic injection of adenovirus vector

Abstract: Blockade of the CD40-CD40L and CD80/CD86-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…22 Recently, we studied the respective roles of CD80 and CD86 in the immune response against Ad, using antagonist anti-CD80 or anti-CD86 MAbs in combination with anti-CD40L in mice. 23 We observed that the simultaneous blockade of these three molecules upon first vector administration allowed optimal expression of the transgene after a second vector administration. 23 This prompted us to design an experiment in a nonhuman primate model, to verify whether transient costimulation blockade could facilitate readministration of an Ad vector through the systemic route.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…22 Recently, we studied the respective roles of CD80 and CD86 in the immune response against Ad, using antagonist anti-CD80 or anti-CD86 MAbs in combination with anti-CD40L in mice. 23 We observed that the simultaneous blockade of these three molecules upon first vector administration allowed optimal expression of the transgene after a second vector administration. 23 This prompted us to design an experiment in a nonhuman primate model, to verify whether transient costimulation blockade could facilitate readministration of an Ad vector through the systemic route.…”
Section: Introductionmentioning
confidence: 87%
“…23 We observed that the simultaneous blockade of these three molecules upon first vector administration allowed optimal expression of the transgene after a second vector administration. 23 This prompted us to design an experiment in a nonhuman primate model, to verify whether transient costimulation blockade could facilitate readministration of an Ad vector through the systemic route. The interaction between monkey CD40 and CD40L was targeted at the APC side using an antagonist anti-human CD40 MAb, 5D12.…”
Section: Introductionmentioning
confidence: 87%
“…1,6,7 Other studies have compared immune-competent versus immune-compromised manipulated hosts to better understand the biologic mechanisms involved in the immune response induced by Ad vectors. [11][12][13][14][15][16][17][18][19][20][21] Although such studies are crucial to understand the effects of isolated effector molecules on persistence of the Ad transgene, these studies are usually carried out in the same strain of mice, and cannot account for the genetic variability in the immune response in different strains of mice. Therefore, these studies may not be able to represent the various contributions of genetic polymorphisms to eliminate the administered Ad vectors, and thus prevent our understanding of the precaution and limitation of adenoviral gene therapy in immune diversified hosts such as humans.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Inhibition of development of CTL has been achieved by blocking the Th1 helper T-cell response by immunosuppressive therapy, 11 anti-CD4 therapy [12][13][14] anti-TNF therapy, 15 and by therapies that block B7-CD28 signaling and CD40-CD40L interactions. [16][17][18][19][20] We have previously developed cell-gene therapy utilizing either Fas ligand to delete specifically T cells responsive to Ad, or have blocked the hepatocyte to apoptosis with the soluble DR5, both of which result in prolonged gene therapy. 21,22 Therefore, it is clear that crippling of one or more of the effector pathways of the innate or adaptive immune response pathways to Ad gene therapy can greatly inhibit the elimination of Adinfected hepatocytes and greatly prolong gene therapy expression.…”
Section: Introductionmentioning
confidence: 99%
“…One such approach employed antibodies directed against CD40, CD80/B7.1 and CD86/B7.2. 60 This treatment reportedly fully abrogated the immune response against the Ad vector such that readministration was as effective as that in naïve animals. In addition, these authors claimed that the animals were capable of mounting a normal response to Ad.…”
Section: Readministration With Ad Vectors Remains a Challengementioning
confidence: 99%